Analysis of 14 terpenoids and sterols and variety discrimination of Codonopsis Radix using ultra‐high‐performance liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry. Issue 8 (12th March 2023) - Li, Wen; Xu, Xu; Tang, Zhuoshi; Guo, Yina; Fei, Dongqing; Yan, Na; Hu, Fangdi
Abstract : Recently, we confirmed that the 95% ethanol‐extracted fraction of Codonopsis Radix, which contains several triterpenoids and sterols, possesses pharmacological activities. However, due to the low content and diverse types of triterpenoids and sterols, their similar structures, lack of ultraviolet absorption, and difficulty in obtaining controls, few studies have so far assessed their contents in Codonopsis Radix. We accordingly constructed an ultra‐high‐performance liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry technique for the simultaneous quantitative determination of 14 terpenoids and sterols. Separation was performed on the Waters Acquity UPLC HSS T3 C18 column (100 × 2.1 mm, 1.8 μm) with 0.1% formic acid (A) and 0.1% formic acid in methanol (B) as mobile phase under gradient elution. The determination coefficients for each of the matrix calibration curves were ≥0.9925. The average recovery ranged from 81.25% to 118.05%, with relative standard deviations of <4%. The contents of 14 components in 23 batches were quantified and further analyzed through chemometrics. Linear discriminant analysis can distinguish sample varieties. The quantitative analysis method can accurately determine the contents of 14 components and thereby provide the chemical basis for the quality control of Codonopsis Radix. It also could be a valuable approach for the classification of different Codonopsis Radix varieties.